THE EFFECTIVENESS OF INTERCULTURAL COMMUNICATIVE LANGUAGE TEACHING (iCLT) MODEL FOR LEARNING INTERCULTURAL COMMUNICATION: A CASE STUDY - Almalia Nurhidayah (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2022)
Abstract: This study to find out the effectiveness of the effectiveness of the intercultural communicative language teaching model (iCLT) in EFL students' learning experiences of intercultural communication. This study used qualitative research as Methodology and used in-depth information using a variety of data collection, such questionnaires and interviews as research design. The research of this study was held in the second semester in the academic year of 2020/2021. The data was taken from the third grade of of English Education Department on a Private University in Cirebon. The result showed that the the implications of teaching intercultural communicative language (iCLT) on intercultural communication, it can be concluded that most of the effectiveness of the iCLT model in intercultural communication learning is very positive. They gain new learning experiences, understand their own identity in relation to others, and do not adopt a new cultural identity. Even Though, there are still the strengths and weaknesses of each teaching step (Input Notice Practice Output) in the ICLT model. And each step of teaching is part of the ICLT model which aims to accommodate them to become intercultural speakers with ICC and be able to communicate and socialize effectively. and appropriate with other people from different cultures and countries.Keywords: Intercultural Communicative Language Teaching(iCLT) Model, Intercultural Communication (IC), Teaching Step, Intercultural Communicative Competence (ICC), Intercultural.